Estrategias de marketing para el posicionamiento del restaurante Paty de la parroquia El Tingo, del cantón Pujilí - Cedeño Sánchez, Angélica Monserrate (2023)
The objective of the project was to determine the marketing strategies that allow the positioning of the Restaurant Paty in the El Tingo parish. The idea emerged from the problem of the owner’s poor market knowledge, so wasting marketing tools and not taking into account elements of strategic direction. The methodology presented a qualitative approach that allowed studying the problem in its natural context through the vision of its main stakeholders: the owner and the customers of the establishment. The descriptive research allowed to characterize the variables of marketing and positioning strategies. For the approach of the generalities of the Restaurant Paty the inductive-deductive method was used, in addition to the issuance of conclusions and recommendations. The information was collected through the interview directed to the owner and the census of the clients. The universe population included the business owner and 80 frequent customers. For the field investigation, two instruments were designed: a questionnaire for the interview, made up of open questions; and for the census, closed questions with options focused on a Likert scale. The validation was carried out by experts’ judgment and calculation of the Cronbach's Alpha index. The results determined that the relevant positioning factors are: flavor, waiting time, payment methods, product presentation, advertising strategies. For this reason, 7 strategies were proposed around the elements product, price, place, and promotion, so that they were: the design of a logo and slogan, training, motivation for the owner and collaborators, advertising alternatives through social networks, promotional strategies, suggestion for the implementation of home delivery service, payments through bank transfers, mobile payment by using “De Una” service, and the location of a complaints mailbox. With the development of the proposal, the owner and collaborators would benefit directly, the clients indirectly and suppliers of El Tingo parish.